Romanians’ attitudes towards mobility for work from a gendered perspective - SĂNDULEASA, Andra-Bertha (Annals of Spiru Haret University. Economic Series, 2016)
Employment strategies in the European Union laid stress on the importance and on the need to increase the participation of women on labour market. On the other hand, evidence shows that international migration has been feminised in Europe and that, in the past decades, geopolitical conflicts and economic restructuring in Eastern Europe and the Third World generated new patterns of female migration. This article explores Romanians’ attitudes towards mobility for work from a gendered perspective. Based on the Special Euro-barometer 337 – Geographical and labour market mobility – conducted in 2009 on behalf of the European Commission, the main findings of the article are that gender is an important aspect in analysing people’s economic behaviour. The research argues that in order to increase women’s participation on labour market, a deeper understanding of the situation of females on labour market is required.